Temporal Lobe Epilepsy: What do we understand about protein alterations?. (15th June 2021) - Perveen, Nadia; Ashraf, Waseem; Alqahtani, Faleh; Fawad Rasool, Muhammad; Samad, Noreen; Imran, Imran
Abstract: During neuronal diseases, neuronal proteins get disturbed due to changes in the connections of neurons. As a result, neuronal proteins get disturbed and cause epilepsy. At the genetic level, many mutations may take place in proteins like axon guidance proteins, leucine‐rich glioma inactivated 1 protein, microtubular protein, pore‐forming, chromatin remodeling, and chemokine proteins which may lead toward temporal lobe epilepsy. These proteins can be targeted in the future for the treatment purpose of epilepsy. Novel avenues can be developed for therapeutic interventions by these new insights. Abstract : Peodic chest pain, with bloody pleural effusion, should raise the suspicion of pleural endometriosis as a well known, but rare condition in clinical practice.